Keputusan Pembelian Produk Handphone Samsung Mahasiswa Fakultas Ekonomi Universitas Krisnadwipayana dipengaruhi oleh Promosi melalui Minat Beli Sebagai Variabel Mediasi - Nugraha, Naufal Surya; Silitonga, Eddy Sanusi (Program Studi Magister Manajemen Fakultas Ekonomi Universitas Krisnadwipayana, 2026)
The purpose of this study was to determine whether the purchasing decision of Samsung mobile phone products among students of the Faculty of Economics, Krisnadwipayana University was influenced by promotions through purchase intention as a mediating variable. The method used in this study was a quantitative method. The sample used in this study was selected using a probability sampling technique with a simple random sampling approach, where the sample consisted of each individual in the population having an equal opportunity to be selected. The data collected were analyzed using path analysis techniques. The results of the study showed that: (1) Promotion has a positive and significant influence on purchasing decisions. (2) Purchase intention has a positive and significant influence on purchasing decisions. (3) Promotion has a positive and significant influence on purchase intention. (4) Promotion is not influenced by purchasing decisions through purchase intention, with the coefficient of direct influence being greater than the indirect influence.